Secure transmission for uplink and downlink non-orthogonal multiple access system with imperfect channel state information - Dinh-Thuan Do; Minh-Sang Nguyen (Universitas Ahmad Dahlan, 2022)
In this paper, we design a secure transmission scheme in uplink and downlink of non-orthogonal multiple access (NOMA) system. In this scenario, two pairs of base stationuser can operate under the presence of eavesdropper. The relay plays an important role to forward signals from group of base stations to serve distant users. However, the eavesdropper can overhear signal which leads to secure performance need be reconsidered. To provide secure performance, we derive the closed-form expressions for strictly positive secrecy capacity (SPSC). In addition, we rely on relay for enlarge coverage area. The channel conditions meet imperfect channel state information (CSI) which shows degraded secure performance. Results confirm the relationship between transmit power at the source and and SPSC how many main parameters affecting secure performance metric. Furthermore, simulation results show that the uplink and downlink NOMA technique improves secure performance in the low SPSC region. We further conduct analysis by using Monte-Carlo simulations.